2020
DOI: 10.1152/ajplung.00103.2019
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron-based phase-contrast micro-CT as a tool for understanding pulmonary vascular pathobiology and the 3-D microanatomy of alveolar capillary dysplasia

Abstract: This study aimed to explore the value of synchrotron-based phase-contrast microcomputed tomography (micro-CT) in pulmonary vascular pathobiology. The microanatomy of the lung is complex with intricate branching patterns. Tissue sections are therefore difficult to interpret. Recruited intrapulmonary bronchopulmonary anastomoses (IBAs) have been described in several forms of pulmonary hypertension, including alveolar capillary dysplasia with misaligned pulmonary veins (ACD/MPV). Here, we examine paraffin-embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 43 publications
2
36
0
1
Order By: Relevance
“…Three-dimensional imaging of term human umbilical cords, using synchrotron-based phase contrast micro-CT with effective pixel size 1.63 × 1.63 μm 2 ( Norvik et al, 2020 ) and histology, identified a much thicker tunica media (TM) in the umbilical artery than in the vein, with a visibly different structure ( Figure 1a–c , Figure 1—figure supplement 1a–c , Figure 1—videos 1 , 2 ). Most umbilical arteries were occluded at birth independent of delivery method or cord region analyzed, whereas umbilical veins remained patent ( Figure 1b , Figure 1—figure supplement 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional imaging of term human umbilical cords, using synchrotron-based phase contrast micro-CT with effective pixel size 1.63 × 1.63 μm 2 ( Norvik et al, 2020 ) and histology, identified a much thicker tunica media (TM) in the umbilical artery than in the vein, with a visibly different structure ( Figure 1a–c , Figure 1—figure supplement 1a–c , Figure 1—videos 1 , 2 ). Most umbilical arteries were occluded at birth independent of delivery method or cord region analyzed, whereas umbilical veins remained patent ( Figure 1b , Figure 1—figure supplement 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…Abb. 5 [27,28]. Kongenitale Fehlbildungen von Herz, Niere oder Gastrointestinaltrakt sind zusätzlich in über 50 % der Fälle zu beobachten [26].…”
Section: Diffuse Entwicklungsstörungen Des Lungenparenchyms (A1)unclassified
“…Since previous virtual histology applications at synchrotron as well as at laboratory setups were largely limited to smallanimal models (Albers et al, 2018;Busse et al, 2018;Dejea et al, 2019) or to post mortem human tissue (Tö pperwien et al, 2018;Buscema et al, 2019;Vå gberg et al, 2018;Garcia-Canadilla et al, 2018), the extension of the imaging technique to the 3D assessment of clinical biopsies (Norvik et al, 2020;Katsamenis et al, 2019) is now particular timely. Beyond research of tumor patho-physiology, the technique may even be applied in future in a clinical context with potential impact on the diagnosis of and on clinical treatment decisions.…”
Section: Discussionmentioning
confidence: 99%